2018
DOI: 10.1038/s41467-018-05085-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutant ASXL1 cooperates with BAP1 to promote myeloid leukaemogenesis

Abstract: ASXL1 mutations occur frequently in myeloid neoplasms and are associated with poor prognosis. However, the mechanisms by which mutant ASXL1 induces leukaemogenesis remain unclear. In this study, we report mutually reinforcing effects between a C-terminally truncated form of mutant ASXL1 (ASXL1-MT) and BAP1 in promoting myeloid leukaemogenesis. BAP1 expression results in increased monoubiquitination of ASXL1-MT, which in turn increases the catalytic function of BAP1. This hyperactive ASXL1-MT/BAP1 complex promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 63 publications
4
93
0
Order By: Relevance
“…By contrast, mutations involving NPM1 or signaling molecules (e.g., FLT3, RAS gene family) are typically secondary events that occur later during leukaemogenesis [113,114]. Novel promising therapeutic strategies had been established for targeting ASXL1 mutated myeloid malignancies by blocking interactions between ASXL1 and associating epigenetic regulators [115][116][117][118]. Furthermore, recurrent somatic mutations in more than 50 genes have been identified in 80-90% of MDS.…”
Section: Asxl1mentioning
confidence: 99%
“…By contrast, mutations involving NPM1 or signaling molecules (e.g., FLT3, RAS gene family) are typically secondary events that occur later during leukaemogenesis [113,114]. Novel promising therapeutic strategies had been established for targeting ASXL1 mutated myeloid malignancies by blocking interactions between ASXL1 and associating epigenetic regulators [115][116][117][118]. Furthermore, recurrent somatic mutations in more than 50 genes have been identified in 80-90% of MDS.…”
Section: Asxl1mentioning
confidence: 99%
“…Whereas the tumor suppressive role has been attributed to BAP1's important involvement in DNA double strand breakage repair [37], there is emerging evidence that BAP1 can also promote tumor growth when it is overexpressed in particular molecular environments. For example, target genes of BAP1 deubiquitination include mutant ATRX in myeloid neoplasms [25] and Krüppellike factor 5 (KLF5) in basal-like breast cancers [24], which both become stabilized by BAP1 and consequently accelerate tumor growth [24,25]. That BAP1 interacts with KLF5 is of potential interest.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that the mutant ASXL1 and BAP1 form a hyperactive complex to promote myeloid transformation (Fig. 2) [60]. As with wildtype ASXL1, the mutant ASXL1 also contains the ASXH domain (also referred to as DEUBAD), which is essential for interacting with BAP1.…”
Section: The Monoubiquitinated Mutant Asxl1 Forms a Hyperactive Complmentioning
confidence: 99%
“…Bap1-depleted mice showed substantial retention of H2AK119ub and increased the level of H3K27me3 [55]. On the other hand, expression of the mutant ASXL1 results in dysregulation of HOXA gene and reduction of both H2AK119ub and H3K27me3 at HOXA loci [43,45,60,65]. In classical view, CBX recognizes H3K27me3 catalyzed by PRC2 complex followed by recruiting of PRC1 complex to H3K27me3 and subsequent ubiquitination of H2AK119 [73].…”
Section: Regulation Of Hoxa Gene Expression By H2ak119ub Modificationmentioning
confidence: 99%